Impaired redox status and cytochrome coxidase deficiency in patients with polymyalgia rheumatica. Issue 11 (1st November 2001) - Chariot, P; Chevalier, X; Yerroum, M; Drogou, I; Authier, F-J; Gherardi, R
Abstract : OBJECTIVE: To evaluate redox status and muscular mitochondrial abnormalities in patients with polymyalgia rheumatica (PMR). METHODS: Prospective evaluation of deltoid muscle biopsy in 15 patients with PMR. Fifteen subjects matched for age and sex, with histologically normal muscle and without clinical evidence of myopathy, were used as controls. Cryostat sections of muscle were processed for conventional dyes, cytochrome c oxidase (COX), usual histochemical reactions, and Sudan black. A total of 300–800 fibres was examined in each case. Blood lactate, pyruvate, and lactate/pyruvate ratio were determined in all patients. RESULTS: Ragged red fibres were found in eight patients with PMR and accounted for 0–0.5% of fibres. Focal COX deficiency was found in 14 (93%) of 15 patients and in nine (60%) of 15 controls. COX deficient fibres were more common in patients with PMR (range 0–2.5%; mean 0.9%) than in controls (range 0–1.2%; mean 0.3%) (paired t test, p=0.001). Seven (47%) of 15 patients had high blood lactate levels (1.50–2.60 mmol/l) or high blood lactate/pyruvate ratios (22–25). CONCLUSIONS: PMR is associated with mitochondrial abnormalities not solely related to the aging process.